RESPONSE OF GROWTH AND YIELD OF TWO VARIETY OF SOYBEAN (Glycine Max . ( L ) Merrill ) TO AVAILABLE SOIL WATER DEPLETION - Panalosa, Dody (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
All this time, efforts to improve soybeanproductivity is still based onthe expansion of planting area (Badan Pusat Statistik, 2013), but production is still declining. It is also influenced by the lack of understanding about the cultivation of soybeans and the price is less promising causing farmers are reluctant to plant soybeans. This research aims to investigate the response of the growth and productionof two varieties of soybean (Glycinemax. (L) Merrill) to some degree of available soil water depletion. This research was conducted at the Laboratory of Integrated Courses Faculty of Agriculture, University of Lampung, in May up to August 2014, using factorial design in a completely randomized designwith the first factor is depletion of groundwater available (P) which is composed of four levels of available soilwater depletion treatment (ATT) is the treatment P1 (0-20%),P2 (0-40%), P3 (0-60%), and P4 (0-80%) and the second factor, namely soybean varieties (V), which consists of varieties V1 (Wilis) and V2 (Kaba), with three repetitions. Results were analyzed by F test at LSD further by 5%and 1% by using Statistix8 Program. The results showed that the effect of the level of available soilwater depletionduring the vegetative stage and generative phase did not significantly affect plant growth and crop yield. The highest production yield andWilis varieties Kaba obtained at a rate of 0-40%thinning. Based on these values concluded that to produce optimal production in both varieties can still bemaintained until the level of depletion of available soilwater content to 40%. Keyword : Available SoilWater,Depletions, Generative Phase, Vegetative Phase, Yield.